2005
DOI: 10.1128/mcb.25.1.44-59.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of hTid-1, the Human Homolog of Drosophila Tumor Suppressor l(2)Tid, in the Regulation of NF-κB Activity and Suppression of Tumor Growth

Abstract: hTid-1, a human homolog of the Drosophila tumor suppressor l(2)Tid and a novel DnaJ protein, regulates the activity of nuclear factor B (NF-B), but its mechanism is not established. We report here that hTid-1 strongly associated with the cytoplasmic protein complex of NF-B-IB through direct interaction with IB␣/␤ and the IKK␣/␤ subunits of the IB kinase complex. These interactions resulted in suppression of the IKK activity in a J-domain-dependent fashion and led to the cytoplasmic retention and enhanced stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 44 publications
(71 reference statements)
0
48
1
Order By: Relevance
“…With regard to the NF-B pathway with DNAJ proteins, Cheng et al (63,64) have demonstrated that overexpression of DNAJA3 suppresses IB phosphorylation by IKK␤ and, thereby, concluded that DNAJA functions as a negative regulator of NF-B. Our study also indicates a role for DNAJA3 in IB phosphorylation, but our conclusion is opposite that of previous studies.…”
Section: Discussioncontrasting
confidence: 57%
“…With regard to the NF-B pathway with DNAJ proteins, Cheng et al (63,64) have demonstrated that overexpression of DNAJA3 suppresses IB phosphorylation by IKK␤ and, thereby, concluded that DNAJA functions as a negative regulator of NF-B. Our study also indicates a role for DNAJA3 in IB phosphorylation, but our conclusion is opposite that of previous studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, interaction with Smad7 was shown to alter the development of chicken embryos by inhibiting the signaling induced by BMP. Although the DnaJ cysteine-rich domain is essential for the hTid1/STAT5b interaction, we cannot rule out the contribution of the DnaJ domain amino terminus in regulating the expression of STAT5b because this domain plays a role in the targeted degradation of intracellular proteins, as has been observed for the IB-IKK complex (42). Although the physiological function of hTid1 in hematopoietic cells remains currently poorly documented, our findings and published reports suggest that hTid1 may regulate the proliferation and/or survival of hematopoietic cells (60).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in hTid1-mediated growth suppression remain elusive because hTid1 modulates the activity of many proteins involved in signal transduction and hence in the survival/apoptosis and/or cell proliferation. Indeed, hTid1 regulates the activity and/or stability of the tyrosine kinase JAK2, the IKK-IK␤ complex, and therefore the activation of NFB as well as the HIF1␣ transcription factor (42,43,63). In addition, hTid1 interacts with the tumor suppressor APC (adenomatous polyposis coli) and regulates the activity of p53 by affecting its subcellular localization (64,65).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations